Study of Surface Drainage of the University Campus - Rincón, Maribet; Rincón, Benedicto (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
The study consists on the evaluation of the University Campus drainage system by the application of a model for maxima hydrological events, that determined the design flows for return periods of 25 and 50 years. Once defined the runoff, the existent natural and artificial drainages were evaluated, turning out to be inefficient for the transport of these flows; therefore, hydraulic structures were designed for new sections corresponding to the hydraulic design. The structural calculations for the system of collectors, bridges, sewers and channels were carried out with the purpose of determining their dimensions, using a maintenance approach, in order to drain efficiently the study area